Dendritic cells, engineered to overexpress 25‐hydroxyvitamin D 1α‐hydroxylase and pulsed with a myelin antigen, provide myelin‐specific suppression of ongoing experimental allergic encephalomyelitis. Issue 7 (31st March 2017) - Li, Chih‐Huang; Zhang, Jintao; Baylink, David J.; Wang, Xiaohua; Goparaju, Naga Bharani; Xu, Yi; Wasnik, Samiksha; Cheng, Yanmei; Berumen, Edmundo Carreon; Qin, Xuezhong; William Lau, Kin‐Hing; Tang, Xiaolei
ABSTRACT: Multiple sclerosis (MS) is caused by immune‐mediated damage of myelin sheath. Current therapies aim to block such immune responses. However, this blocking is not sufficiently specific and hence compromises immunity, leading to severe side effects. In addition, blocking medications usually provide transient effects and require frequent administration, which further increases the chance to compromise immunity. In this regard, myelin‐specific therapy may provide the desired specificity and a long‐lasting therapeutic effect by inducing myelin‐specific regulatory T (Treg ) cells. Tolerogenic dendritic cells (TolDCs) are one such therapy. However, ex vivo generated TolDCs may be converted into immunogenic DCs in a proinflammatory environment. In this study, we identified a potential novel myelin‐specific therapy that works with immunogenic DCs, hence without the in vivo conversion concern. We showed that immunization with DCs, engineered to overexpress 25‐hydroxyvitamin D 1α‐hydroxylase for de novo synthesis of a focally high 1, 25‐dihydroxyvitamin D concentration in the peripheral lymphoid tissues, induced Treg cells. In addition, such engineered DCs, when pulsed with a myelin antigen, led to myelin‐specific suppression of ongoing experimental allergic encephalomyelitis (an MS animal model), and the disease suppression depended on forkhead‐box‐protein‐P3(foxp3) + Treg cells. Our data support a novel concept that immunogenic DCs can be engineered for myelin‐specific therapy for MS.—Li, C.‐H., Zhang, J., Baylink, D. J., Wang, X., Goparaju, N. B., Xu, Y., Wasnik, S., Cheng, Y., Berumen, E. C., Qin, X., Lau, K.‐H. W., Tang, X. Dendritic cells, engineered to overexpress 25‐hydroxyvitamin D 1α‐hydroxylase and pulsed with a myelin antigen, provide myelin‐specific suppression of ongoing experimental allergic encephalomyelitis. FASEB J. 31, 2996–3006 (2017). www.fasebj.org